Family mealtime emotions and food parenting practices among mothers of young children: Development of the Mealtime Emotions Measure for Parents (MEM‐P) - Hannah J. White; Caroline Meyer; Zoe Palfreyman; Emma Haycraft (Wiley, 2022)
Abstract Family mealtimes can be important for supporting children's healthy development, yet the emotional context of mealtimes can vary considerably, likely impacting their overall success and enjoyment. Yet, despite having an important role, little is known about how parents emotionally experience mealtimes with their family. The first aim of the current study was to assess the factor structure of a novel self‐report measure to assess parents' emotional responses experienced during family mealtimes (Mealtime Emotions Measure for Parents; MEM‐P). The second aim was to examine relationships between maternal mealtime emotions and their food parenting practices. Mothers of children aged between 1.5 and 6 years participated in this study. Mothers were invited to complete an online questionnaire measuring family mealtime emotions, anxiety, depression and food parenting practices. Exploratory factor analysis produced a three‐factor solution comprising both positive and negative emotion subscales: MEM‐P Efficacy; MEM‐P Anxiety; MEM‐P Stress and Anger. Mothers' positive mealtime emotions (mealtime efficacy) were related to greater use of practices promoting autonomy, providing a healthy home food environment, and modelling healthy eating. Higher anxiety about mealtimes was related to greater reports of child control over eating, and mealtime stress and anger was associated with greater use of food to regulate emotions. These findings highlight novel relationships between how mothers emotionally experience family mealtimes and the food parenting practices they use with their children. It is important to develop resources to help promote positive maternal experiences of family mealtimes and food‐based interactions.